Bioelectricity of Various Carbon Sources on Series Circuit from Microbial Fuel Cell System using Lactobacillus plantarum - Mufid Ainun; Linda Suyati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Study on bioelectrisity various carbon sources on the circuit series Microbial Fuel Cell using Lactobacillus plantarum has been conducted. This study aims to determine the electrical energy generated by various types of substrates in MFC and determe the effect of a series circuit of the electrical energy produced using Lactobacillus plantarum. The research stage consisted of preparation stages MFC components, electrical power measurements on variations in the type of substrate, and the measurement of electrical power in series circuit variation. Electrical power measurements were performed on a variety of substrate types by comparing the electrical power generated by the fructose, lactose and starch substrates while the electric power measurements with series variations are used in single series, series 2 and series 3. The results of the maximum electrical power measurement on the variation of fructose, lactose and starch substrate in MFC system using Lactobacillus plantarum were obtained respectively 10,26 mW; 63 mW and 27.47 mW. The maximum electric power generated in the MFC system uses Lactobacillus plantarum in a single circuit, series 2, series 3 series with lactose substrate obtained respectively of 63 mW, 164.74 mW and 290.51 mW. The measurement of electrical power showed that the lactose substrate produces a greater power than the other substrates. Series circuit capable of increasing electrical power in MFC system.